2021
DOI: 10.1126/sciimmunol.abc9801
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor Bcl11b promotes both canonical and adaptive NK cell differentiation

Abstract: Epigenetic landscapes can provide insight into regulation of gene expression and cellular diversity. Here, we examined the transcriptional and epigenetic profiles of seven human blood natural killer (NK) cell populations, including adaptive NK cells. The BCL11B gene, encoding a transcription factor (TF) essential for T cell development and function, was the most extensively regulated, with expression increasing throughout NK cell differentiation. Several Bcl11b-regulated genes associated with T cell signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 89 publications
6
54
0
Order By: Relevance
“…Next, we sought a transcriptional basis for the observed alteration in NK homeostasis. Several recent papers have described the transcriptome of NK cells related to differentiation stages using bulk or single-cell RNA sequencing showing a distinct profile of the immature CD56 bright NK cell subset 9,10,38 . Given the relative increase in CD56 bright NK cells in patients with perturbed NK cell homeostasis, the transcriptional profiles were compared with both bulk and sorted CD56 bright NK cells from healthy donors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we sought a transcriptional basis for the observed alteration in NK homeostasis. Several recent papers have described the transcriptome of NK cells related to differentiation stages using bulk or single-cell RNA sequencing showing a distinct profile of the immature CD56 bright NK cell subset 9,10,38 . Given the relative increase in CD56 bright NK cells in patients with perturbed NK cell homeostasis, the transcriptional profiles were compared with both bulk and sorted CD56 bright NK cells from healthy donors.…”
Section: Discussionmentioning
confidence: 99%
“…CD56 dim NK cells can be subdivided according to expression of the inhibitory receptor NKG2A, killer-immunoglobulin-like receptors (KIR) and the carbohydrate epitope CD57, which associates with changes in functionality as well as longevity 6,7,8 . Recent studies have revealed a set of regulatory gene circuits that reciprocally regulate NK cell differentiation, including TCF7-LEF1, MYC and RUNX2 associated with the early CD56 bright stage and PRDM1-ZEB2 and BCL11B associated with the CD56 dim stage and CMV-induced adaptive NK cell expansions 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…In breast cancer, CD59 could promote the growth of neoplasm and predict the poorly prognostic status ( 40 ). The transcription factor BCL11B is an important immunoregulatory factor that can promote the typical and adaptive differentiation of NK cells ( 41 ). Emerging reports have shown that BASP1 could modulate multiple biological behaviors, such as cell proliferation, apoptosis, and differentiation ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…RNA-seq analysis confirmed that upregulation of ANK pathway was evident at 6 months in the Mw group. Apart from upregulation of KLRC2 and B3GAT1 and downregulation of KLRC1, the key transcription factor in the ANK pathway, BCL11b, was persistently upregulated[41]. Downregulation of EAT-2 and PLZF further corroborated the classic gene expression signature of ANK cells.…”
Section: Discussionmentioning
confidence: 97%